Penampilan Ratun dari Galur-Galur Padi KeturunanVarietasLokal Bengkulu pada Lahan Rawa Lebak - Sumardi Sumardi; M. Chozin; Hermansyah Hermansyah (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Sumardi et al, 2016. Ratoon Performances of Rice Lines Generated from Bengkulu Local Varieties on Inland Swamp. JLSO 5(1):71-78.Ratooning offers an opportunity to increase rice production under swampy areas commonly hampered by a limited growing seasons due seasonal water level fluctuation. Present study was undertaken to evaluate the ratoon growth and yield performances of rice lines grown on inland swamp. Eight F4 lines derived from crosses involving Bengkulu local swamp rice varieties (UBPR1, UBPR2, UBPR3, UBPR4, UBPR6, UBPR7, UBPR9, and UBPR10) along with two released varieties (Inpara5 and Inpara 6) were grown on inland swamp under a randomized complete block design with three replications. Data were collected on ratoons emerged following harvest of the main crops for plant height, total tiller number,heading date, productive tiller number, panicle length, grain number per panicle,percent of filled grains per panicle, 100 grain weight, and grain yield per hill. Results indicated significant variations among the genotypes for most of the observed variables, except total tiller number, grain number per panicle, and percent of filled grains per panicle. UBPR10had produced highest total tiller number (12.6) and productive tiller number (11.6). UBPR1 produced the highest panicle length (19.0 cm) and grain number per panicle (66.43). UBPR3 exhibited the tallest (100.13 cm) and highest grain yield per hill (12.023 g), but most delayed heading date (18.0 d). With respect to the productivity of ratoon, UBPR 3 showed the most productive lineby yielding grain 49.54% of the main crop yield.